1991
DOI: 10.1152/jn.1991.65.5.1034
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized GABAergic IPSPs recorded in the neocortex after blockade of synaptic transmission mediated by excitatory amino acids

Abstract: 1. Intracellular and extracellular recordings were carried out in guinea pig neocortical slices to examine the effects of blockade of excitatory amino acid (EAA) synaptic transmission on population discharges elicited by 4-aminopyridine (4-AP; 50-100 microM). 2. After the introduction of 4-AP, two distinct types of rhythmic spontaneous field potentials were recorded in neocortical slices. Type I consisted of multiple spike discharges lasting 20-90 s. These events occurred at a frequency of 0.4-0.2/min. Type II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…The contribution of GABA A receptors to the 4AP-induced slow, interictal events recorded during blockade of glutamatergic receptors is further supported by intracellular data obtained from principal cells in the neocortex (Aram et al, 1991;Avoli et al, 1994), hippocampus (Perreault and Avoli, 1992) and in other limbic areas such as the amygdala or the entorhinal cortex. In all cases, the counterpart of the slow discharges that continue to occur in the presence of glutamatergic receptor antagonists is a sequence of hyperpolarizingdepolarizing potentials that change in amplitude as expected for a post-synaptic response due to Cl − conductances (Fig.…”
Section: Involvement Of Gaba a Receptor-mediated Mechanisms In The Slowmentioning
confidence: 63%
See 1 more Smart Citation
“…The contribution of GABA A receptors to the 4AP-induced slow, interictal events recorded during blockade of glutamatergic receptors is further supported by intracellular data obtained from principal cells in the neocortex (Aram et al, 1991;Avoli et al, 1994), hippocampus (Perreault and Avoli, 1992) and in other limbic areas such as the amygdala or the entorhinal cortex. In all cases, the counterpart of the slow discharges that continue to occur in the presence of glutamatergic receptor antagonists is a sequence of hyperpolarizingdepolarizing potentials that change in amplitude as expected for a post-synaptic response due to Cl − conductances (Fig.…”
Section: Involvement Of Gaba a Receptor-mediated Mechanisms In The Slowmentioning
confidence: 63%
“…Moreover, Benardo (1997) has shown that during 4AP application neocortical interneurons generate sustained action potential firing. Finally, long-lasting depolarizations with associated firing have been reported to occur in principal cells of the neocortex (Aram et al, 1991;Avoli et al, 1994) and of the cingulate cortex (Panuccio et al, 2009) during 4AP treatment.…”
Section: Involvement Of Gaba a Receptor-mediated Mechanisms In The Slowmentioning
confidence: 97%
“…This is supported by the fact that LLDs remained coupled in all areas of the slice after the addition of both NMDA and non-NMDA antagonists that block fast synaptic transmission of many pathways in the hippocampus (Neumann et al, 1988;Davies and Collingridge, 1989;Lambert et al, 1989). Recent observations in the neocortex have also shown that the occurrence of GABA-mediated slow depolarizations is resistant to excitatory amino acid antagonists (Aram et al, 1991).…”
Section: -Ap and Epileptiform Activitymentioning
confidence: 90%
“…Currently, there is strong evidence favouring GABA, not glutamate, as the important excitatory neurotransmitter coordinating neuronal network maturation during development by inducing giant depolarizing potentials (GDPs; Ben-Ari et al, 1989;Kasyanov et al, 2004;Krnjevic, 2004;Ben-Ari and Holmes,2005). GABA has also been observed to exert excitatory postsynaptic effects in adult hippocampal slices in response to high frequency stimulation or intense dendritic activation (Staley et al, 1995;Lamsa and Taira, 2003;Krnjevic, 2004), and in the presence of 4AP (Perreault and Avoli, 1989;Aram et al, 1991;Michelson and Wong, 1991;Lamsa and Kaila, 1997).…”
Section: Gaba-mediated Synchronicity and 4-aminopyridinementioning
confidence: 99%